SoTL research methodologies a guide to conceptualizing and conducting the scholarship of teaching and learning - Yeo, Michelle M. L.; Manarin, Karen; Miller-Young, Janice (New York, NY Routledge, Taylor & Francis Group, 2024)
Combining real examples with a roadmap of how to construct studies, analyze results, and share work, this book serves as a primary research methodology text for the field of Scholarship of Teaching and Learning (SoTL). The volume seeks to explore key aspects of SoTL that are often missing in past frameworks: research-based ontologies, epistemologies, and ethical axiologies. Chapters map out the expansive continuum of SoTL by detailing its history and key work while incorporating Indigenous perspectives on pedagogy and research methodologies. The text also features methods of qualitative and quantitative data generation essential for SoTL such as conducting interviews and focus groups, procuring data through questionnaires and artifact observation, and sharing results for dissemination in traditional and public scholarship. A comprehensive guide for conducting SoTL research, this book illustrates a broad array of contexts and a spectrum of research methodologies to expand, enrich, and support both novice and experienced SoTL practitioners and researchers in answering the contexts and questions at the heart of teaching and learning"--
Understanding SoTL -- Developing SoTL inquiries -- Thinking about SoTL research frameworks -- Generating quantitative data and constructing questionnaires -- Interviews and focus groups -- Artifacts, observations, and reflections -- Quantitative research designs and statistical analysis -- Empirical qualitative approaches -- Mixed methods research designs -- Interpretive research -- Transformative methodologies -- Academic genres -- Communicating visually : ideas and data -- Amplifying your research.
Includes bibliographical references.
Keywords: Learning and scholarship; Learning -- Research -- Methodology; Teaching -- Research -- Methodology